Flexibility in Coordination Polymers: Structure, Topology, Porosity, and Addressability - SENSHARMA, DEBOBROTO (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
Metal-Organic Frameworks (MOFs) are a research area approaching maturity and the industrial application of MOFs to a number of pressing challenges is imminent. These materials are exciting for their porosity and chemical tunability, as well as the applicability of rational principles in their design. MOFs are applied in fields as diverse as gas storage and separation, drug delivery, catalysis, and sensing. The design of MOFs is guided by a few powerful general principles that form the basis of the approach known as reticular chemistry. The reticular approach emphasises symmetric structures obtained by the use of rigid organic components. In this thesis, a variety of non-rigid behaviours are examined, such as the accommodation of torsional strain in one- and two-dimensional coordination polymer motifs, the diversity of conformations accessible to ligands due to free rotations in alkyl-chain backbones or ethynyl spacers, rotational flexibility about metal-ligand bonds in assembled MOFs, and conformational variability about p-phenylene spacers in extended ligands. In the absence of perfectly rigid organic linkers, or in frameworks that allow a degree of internal motion, new and unusual topologies are obtained due to lower-symmetry conformations. These effects are combined with chemical functionality resulting in MOFs that respond to stimuli, such as light or moisture, with changes in structure that reversibly affect porosity. In chapter 1, chemical and historical contexts for the strategies adopted and results presented in this work are described. A brief history and description of the concepts used is provided, followed by a survey of the current literature in the field and the progress made in the various applied branches of MOF chemistry. The aims of the thesis are delineated. In chapter 2 mixed-ligand one- and two-dimensional coordination polymers based on various M2+ metal ions are described. Both ligands used are tripodal. The accommodation of varying M2+ ion radii takes place in 1-4 due to the ability of the ligands used to adopt increasingly strained conformations. This effect permits the recurrent formation of the same one-dimensional coordination polymer motif, and the same packing arrangement in two dimensions. However, supramolecular packing in the third dimension, mediated by aromatic interactions between distorted ligands, varies as a result of increasing ionic radius. The chelating ligand used in 1-4 is replaced with an isomeric capping ligand, and a two-dimensional sheet motif is obtained. This mixed ligand strategy is applied to ditopic N-donor ligands used in combination with ditopic organic and inorganic charged moieties in Chapter 3. Functionalised ligands are used as pillars in 3D structures which contain accessible 1D channels in 6 and 7. Prolonged and delicate crystallisations allowed the isolation of compounds based on N-donor ligands with highly flexible alkyl-chain backbones ? 8 and 9, which were both found to be two-dimensional, rather than the three-dimensional structures shown by homologues. 8, was shown to be intrinsically porous, and showed excellent CO2 uptake characteristics and selectivity, bringing the most valuable qualities of many 3D MOFs into two dimensions. The ditopic, bridging monodentate coordination mode adopted by the aromatic 4,4?-azopyridine ligand in 10 allows it to pivot about its axis in response to its surroundings. This led to the occurrence of a sharp transition upon the adsorption of 1.5 molecules of CO2 molecules per unit cell, after which the uptake of CO2 increased dramatically. 10 was shown to be selective for CO2 over N2, and the stimulus-responsive behaviour was shown to result in the highest room temperature CO2 working capacity between 0.1 bar and 1 bar recorded till date. A reversible transition also occurs between 10 and a hydrated phase 10′, which is utilised for the instantaneous release of adsorbed CO2 from 10. In Chapter 4, an elegant synthetic strategy is described, by which neutral, ditopic, N-donor ligands of appropriate length were incorporated into frameworks with the pto topology. This may be considered a mixed ditopic+tritopic ligand strategy. 11 and 12 were built by the incorporation of the photoresponsive 4,4?-azopyridine ligand into pto scaffolds built with highly extended, flexible ligands. As a result, the photoresponsivity of the 4,4?-azopyridine ligand is expressed through static and dynamic changes in the CO2 uptake of 11 and 12. Strong responses to irradiation ? changes of 40% of the magnitude of uptake under dynamic irradiation conditions ? are observed. 11 and 12 are the first reported MOFs with photoresponsive gas uptake in which photoswitching ligands are not the sole organic component. This synthetic strategy was also used to incorporate functionalised ditopic ligands into pto scaffolds in 13-16. Chapter 5 contains a description of novel MOFs based on the highly extended bteb3- and bbc3- ligands and analyses of their structures. Conformational flexibility due to the acetylene and p-phenylene spacers allows the adoption of otherwise inaccessible dihedral angles, and lower symmetry conformations. As a result, the frameworks in 17-23 form ?non-default? networks. In 19 and 23, 4,4?-azopyridine is used as an auxiliary ligand, and novel topologies are obtained. In Chapter 6, a number of MOFs (24-28) are described which were targeted for specific attributes using the bteb3- and bbc3- ligands. Simulations are carried out to show the potential porosities of these frameworks, and some exceptional attributes are observed. Chapter 7 describes the experimental details of the work carried out. Chapter 8 concludes the thesis and offers an outline of the research questions emerging from the results presented which may be addressed in future studies.
APPROVED
Keywords: MOFs; Coordination Polymers; Topology; Porosity